Percutaneous removal of unraveled HELEX® septal occluder 4 months post deployment. Issue 1 (25th February 2015) - Suntharos, Patcharapong; Komarlu, Rukmini; Prieto, Lourdes R.
<x xml:space="preserve">Abstract</x> The GORE® HELEX® Septal Occluder (HSO: W.L. Gore & Associates; Flagstaff, AZ) is preferentially used at our institution for percutaneous closure of the patent foramen ovale (PFO). Adequate deployment of the device requires capture of three sequential eyelets by the locking loop. At times, the right atrial eyelet is not caught, particularly when a long tunnel PFO causes too much separation between the discs. Although rarely, unlocked devices have been left in the atrial septum with no untoward events provided they appear stable in the catheterization laboratory and the shunt has been eliminated. We report a patient in whom an unlocked, but otherwise well positioned, HSO subsequently unraveled with the right atrial disc migrating through the tricuspid valve while the left atrial disc remained well apposed to the left side of the atrial septum. The PFO was closed prior to liver transplantation to prevent an embolic event during the transplant. The patient required placement of several internal jugular central lines prior to transplant, and this instrumentation in the right atrium may have caused unraveling of the device. The HSO was removed percutaneously 15 weeks after implantation despite a well‐seated and likely partially endothelialized left atrial disc. © 2015 Wiley Periodicals, Inc.